PENGARUH KECERDASAN LOGIS MATEMATIS TERHADAP KEMAMPUAN MENYELESAIKAN SOAL CERITA MATA PELAJARAN MATEMATIKA KELAS VIII SMP NEGERI 1 GUNUNGSARI TAHUN AJARAN 2022/2023 - Darajatul Khunul Khotimah; Amrullah; Baidowi; Nyoman Sridana (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2023)
Mathematical logical intelligence is a factor influences students’ ability to solve story problems. It is related to reasoning and arithmetic. Students who have it can solve story problems easily and precisely. This research aims to determine and describe the influence of mathematical logical intelligence on students' ability to solve story problems in mathematics subjects This research is a quantitative research with the type of ex-post facto research. The population used in this research was 161 class VIII students and a sample of 32 students who were given instruments in the form of questionnaires and easy tests to complete. The data analysis used is inferential statistical analysis. The results of the regression coefficient test obtained a value of  with the regression equation    which was very significant, where  is students' mathematical logical intelligence, and  is the ability to solve student story problems. The results of the correlation coefficient analysis (r) results were 0.550 with a contribution of 30.3%. It can be concluded that mathematical  logical intelligence influence students' ability to solve story problems in class VIII mathematics subjects at SMP Negeri 1 Gunungsari for the 2022/2023 academic year. If a student's mathematical logical intelligence increases by one unit, the student's ability to solve story problems increases by 0.506.